Pengaruh DER, Komisaris Independen, dan Kepemilikan Institusional terhadap ROE : (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI tahun 2015-2019) - Ida Adhani; Rahmawati Rahmawati (Owner : Riset dan Jurnal Akuntansi, 2021)
This study aims to estimate and analyze the factors that affect ROE (Y), either partially or jointly. In this study, the factors tested were DER (X1), Independent Commissioner (X2) and Institutional Ownership (X3). The research method used is multiple linear regression analysis, with purposive sampling method on 7 metal and similar sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This study uses secondary data obtained from evidence, notes, historical reports compiled in the annual financial statements obtained from the internet site, namely www.idx.co.id. The statistical method used is inferential statistics, using multiple linear regression models. As for what is tested in the classical assumption test inferential statistics, R2 test, T test and F test. The test results show that the DER variable has a significant effect on ROE, institutional ownership has no effect on ROE, institutional ownership has no significant effect on ROE. The results of the F test show that DER, Institutional Ownership, and Independent Commissioner simultaneously have a significant effect on ROE.